George Soros on Globalization - Soros, George (New York PublicAffairs, 2002)
"Even before September 11, 2001, it was clear that not everyone was happy with globalization: violent protests have become a regular feature of international summit meetings, and many young people have expressed their strong opposition to policies that they see as enriching the rich at the expense of workers, the environment, and traditional culture." "In this book, Soros not only identifies the problems but also puts forward practical proposals to make the system work better. In a thoughtful analysis of our existing international financial and trade institutions, Soros shows that while they aid wealth creation they fall short in providing other public goods.
Include Index
Keywords: International Economic Relations -- International Trade -- International Finance -- Globalization--Economic Aspects -- World Trade Organization -- International Monetary Fund